2021
DOI: 10.1002/ejoc.202101093
|View full text |Cite
|
Sign up to set email alerts
|

Step‐Economical Route to 2‐Amido‐3‐bromobenzo[b]thiophenes via Ynamide Formation and Selectfluor‐Mediated Oxidative Bromocyclization

Abstract: A one‐pot synthesis of 2‐amido‐3‐bromobenzo[b]thiophenes based on C−N coupling and oxidative bromocyclization reactions was developed. This enables a modular approach to obtain diverse substituents at the C2 position of benzothiophenes by employing structurally modified sulfonamides. Oxidative cyclization was driven by Selectfluor and represents a previously unreported recycling method for the bromide anion byproducts of the C−N bond coupling step. The details of the study are described fully herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The 2thioanisole substituted bromoalkyne (3la) afforded a significantly lower yield than the 2-anisole substituted bromoalkyne (3ka) despite the complete conversion of the starting material because 2-amidobenzo [b]thiophene (3la') was formed by an annulation reaction via a keteniminium intermediate when methanol solvent was used. 22 Other types of arene substitutions, such as naphthyl, pyridyl, and thiophenyl, were also well-tolerated under the same conditions, resulting in high yields, respectively (3ma-3oa, 77-100 %). Bromoalkynes with aliphatic groups, such as n-pentyl and phenethyl, were coupled smoothly with sulfonamide 2a to give the corresponding products in good yields (3ma-3na, 72-75 %).…”
Section: Synlettmentioning
confidence: 90%
See 1 more Smart Citation
“…The 2thioanisole substituted bromoalkyne (3la) afforded a significantly lower yield than the 2-anisole substituted bromoalkyne (3ka) despite the complete conversion of the starting material because 2-amidobenzo [b]thiophene (3la') was formed by an annulation reaction via a keteniminium intermediate when methanol solvent was used. 22 Other types of arene substitutions, such as naphthyl, pyridyl, and thiophenyl, were also well-tolerated under the same conditions, resulting in high yields, respectively (3ma-3oa, 77-100 %). Bromoalkynes with aliphatic groups, such as n-pentyl and phenethyl, were coupled smoothly with sulfonamide 2a to give the corresponding products in good yields (3ma-3na, 72-75 %).…”
Section: Synlettmentioning
confidence: 90%
“…Recently, we observed noteworthy results using an alcohol as the solvent, which considerably reduced the reaction time in the Cu-catalyzed alkynylation of sulfonamides using bromoalkynes 22 compared to known procedures using toluene, 8a-d pyridine, 8e and dioxane 19a as solvents. Recent studies on the optimization of C-N coupling have revealed that microwave irradiation significantly accelerates the reaction rate.…”
Section: Template For Synlett Thiemementioning
confidence: 99%